Alasan Turki Melanjutkan Pembelian Persenjataan S-400 Rusia: Analisis Kebijakan Luar Negeri dalam Perspektif Realisme Neoklasik - Priscilia Dewi, Putu Nanda; Wiranata, I Made Anom; Widya Nugraha, A.A. Bagus Surya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2022)
This research aims to describe the reasons for the Turkish Government to continue purchasing Russian S-400 weapons through qualitative-descriptive method. Massive sanctions imposed by the United States as an alliance country that prohibits transactions of weapons from Russia did not affect Turkey's decision to continue purchasing the S-400. Whereas the United States has specifically warned about the security threat that S-400 poses to the NATO alliance, Turkey ignored the warning and continued to process the purchase of this weapon. Therefore, this research uses Neoclassical Realism theoretical perspective by analyzing internal and external factors in answering the reasons behind Turkey's measure to continue the purchase of S-400 agreement with Russia. This research finds that Turkey's decision is a response to systemic pressures, international structures, and domestic factors. Keywords: Turkey’s Foreign Policy, S-400 Armaments, Neoclassical Realism, NATO Alliance Dynamics